Operational Risk in Both Conventional and Islamic Banking Perceptions: Differences and Similarities - Rhanoui, Salma; Belkhoutout, Khalid (European Scientific Journal, ESJ, 2018)
While risks in conventional banks have been meticulously discussed in the literature, they remain a fresh research area in Islamic banks. In this context, operational risk has long been considered a simple part of “other” risks outside the dominion of credit risk and market risk, before it made its way to the forefront of banking. In fact, with the rise and enlargement of the Islamic banking industry and its unique contractual features and legal environment, operational risk has become more wide-ranging in Islamic banks compared to conventional banks. In this sense, the following work aims to provide a comparison of operational risk perceptions in both conventional and Islamic banks, with the objective of determining the fundamental similarities and differences of this risk within each system, which can be seen as a boosting step meant to help creating a good risk management tactics in both banks. This work showed a difference regarding the two definitions of operational risk. It also demonstrated that the conventionnal and Islamic banking systems are similar while presenting some differences in terms of components and factors of opeational risk.